Occupational health policy and immigrant workers in the agriculture, forestry, and fishing sector. Issue 8 (18th April 2013) - Liebman, Amy K.; Wiggins, Melinda F.; Fraser, Clermont; Levin, Jeffrey; Sidebottom, Jill; Arcury, Thomas A.
Abstract Background Immigrant workers make up an important portion of the hired workforce in the Agricultural, Forestry and Fishing (AgFF) sector, one of the most hazardous industry sectors in the US. Despite the inherent dangers associated with this sector, worker protection is limited. Methods This article describes the current occupational health and safety policies and regulatory standards in the AgFF sector and underscores the regulatory exceptions and limitations in worker protections. Immigration policies and their effects on worker health and safety are also discussed. Emphasis is placed on policies and practices in the Southeastern US. Results Worker protection in the AgFF sector is limited. Regulatory protections are generally weaker than other industrial sectors and enforcement of existing regulations is woefully inadequate. The vulnerability of the AgFF workforce is magnified by worker immigration status. Agricultural workers in particular are affected by a long history of "exceptionalism" under the law as many regulatory protections specifically exclude this workforce. Conclusions A vulnerable workforce and high‐hazard industries require regulatory protections that, at a minimum, are provided to workers in other industries. A systematic policy approach to strengthen occupational safety and health in the AgFF sector must address both immigration policy and worker protection regulations. Am. J. Ind. Med. 56:975–984, 2013. © 2013 Wiley Periodicals, Inc.